1980
DOI: 10.1038/284074a0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of sister chromatid exchanges by BUdR is largely independent of the BUdR content of DNA

Abstract: The halogenated thymidine (dT) analogue, 5-bromodeoxy-uridine (BUdR), has a variety of effects on mammalian cells, including toxicity, suppression of differentiation, and mutagenesis. Although it is generally assumed that the effects of BUdR are due primarily to its presence in DNA, results from our laboratory have raised doubts about such assumptions. We have shown, for example, that BUdR mutagenesis in mammalian cells is determined by the concentration of BUdR in the medium rather than in DNA, and that mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
2

Year Published

1980
1980
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(28 citation statements)
references
References 16 publications
0
26
0
2
Order By: Relevance
“…Indeed, IdU has been previously shown to be less efficiently incorporated in DNA than BrdU and CldU (Franken et al, 1997). On the other hand, it has been reported that modulating the concentration of BrdU in the medium favours the occurrence of damages in the replicating DNA by an imbalancing in the ratio between the nucleotide pools leading to frequent BrdU/ guanine mispairing (Davidson et al, 1980(Davidson et al, , 1988. However, the addition of deoxycytidine, which prevents such an effect, even in excess over BrdU or CldU (Davidson et al, 1988), does not affect the association of replicating (halogenated) DNA with BCL6 bodies (unpublished data), suggesting therefore that this association is indeed correlated with the level of incorporation of the halogenated nucleotide into the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IdU has been previously shown to be less efficiently incorporated in DNA than BrdU and CldU (Franken et al, 1997). On the other hand, it has been reported that modulating the concentration of BrdU in the medium favours the occurrence of damages in the replicating DNA by an imbalancing in the ratio between the nucleotide pools leading to frequent BrdU/ guanine mispairing (Davidson et al, 1980(Davidson et al, , 1988. However, the addition of deoxycytidine, which prevents such an effect, even in excess over BrdU or CldU (Davidson et al, 1988), does not affect the association of replicating (halogenated) DNA with BCL6 bodies (unpublished data), suggesting therefore that this association is indeed correlated with the level of incorporation of the halogenated nucleotide into the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that the early S-phase was the stage most sensitive to the chemically induced SCEs, as shown in our results. The increased rate of SCEs after FUdR treatment in the present study may be explained by the hypothesis that SCE frequency depends to some extent on the BUdR concentration (4,9,11,19), and that FUdR inhibits thymidine synthesis which, thus producing efficient incorporation of BUdR into chromosomes (4,5).…”
Section: Discussionmentioning
confidence: 47%
“…Deoxycytidine has been known to counteract an increase of SCEs by excess thymidine and BrdU in normal cells (Davidson et al, 1980;Kaufman, 1986). Purine deoxyribonucleosides (dG and dA) caused a significant concentration-dependent increased in SCE frequency both in normal and BS cells (Table I).…”
Section: Effect O F Deoxynucleosides On the Frequency O F Sister Chromentioning
confidence: 99%